Prevalence of needle-stick injury among nursing students: A systematic review and meta-analysis - Xu, Xu; Yin, Yu; Wang, Hao; Wang, Fengxia (Frontiers in Public Health, 2022)
Introduction Needle-stick injuries (NSI) are a serious threat to the health of healthcare workers, nurses, and nursing students, as they can expose them to infectious diseases. Different prevalence rates have been reported for this type of injury in different studies worldwide. Therefore, this study aimedto estimate the pooled prevalence of NSI among nursing students. Methods This study was conducted by searching for articles in Web of Science, PubMed, Scopus, Embase, and Google Scholar without time limitation using the following keywords: needle-stick, needle stick, sharp injury, and nursing student. The data were analyzed using the meta-analysis method and random-effects model. The quality of the articles was evaluated with Newcastle-Ottawa Quality Assessment Scale (NOS). The heterogeneity of the studies was examined using the I2 index, and the collected data were analyzed using the STATA Software Version 16. Results Initially, 1,134 articles were retrieved, of which 32 qualified articles were included in the analysis. Nursing students reported 35% of NSI (95% CI: 28–43%) and 63% (95% CI: 51–74%) did not report their needle-stick injuries. The highest prevalence was related to studies conducted in Asia (39.7%; 95% CI: 31.7–47.7%). There was no significant correlation among NSI prevalence and age of samples, and article year of publication. Conclusion A third of nursing students reported experiencing NSI. Consequently, occupational hazard prevention training and student support measures need to be considered.